2012
DOI: 10.1007/s11096-012-9642-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drug–drug interaction screening software combined with pharmacist intervention

Abstract: The performance of IM-Pharma combined with pharmacist intervention was positive with an expressive reduction in the risk of DDIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
(26 reference statements)
0
30
0
7
Order By: Relevance
“…This justifies the elevated number of publications in this matter (Rivkin, Yin, 2011;Kane, Weber, Dasta, 2003;Moura et al, 2012;Papadopoulos, Smithburger, 2010;Mannheimer, Eliasson, 2010.;Moreira, Cassiani, 2011).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This justifies the elevated number of publications in this matter (Rivkin, Yin, 2011;Kane, Weber, Dasta, 2003;Moura et al, 2012;Papadopoulos, Smithburger, 2010;Mannheimer, Eliasson, 2010.;Moreira, Cassiani, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…A recent study conducted in the USA showed that 46.3% of ICU prescriptions included pDDIs (Smithburger, Kane-Gill, Seybert, 2012), while Brazilian studies have reported a prevalence of 67% or 70% (Hammes et al, 2008;Moreira, Cassiani, 2011). In addition, there are international differences in drug availability that may contribute to regional variations in the number of pDDIs (Moreira, Cassiani, 2011;Moura, Prado, Acurcio, 2011;Moura et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The committee set up 22 meetings during the study period, attended by a median of 7 professionals [IQR, [6][7][8][9] per meeting. This included a median of 3 pharmacists [IQR, [3][4] for a median of 1.5 technicians [IQR, 1-2] per meeting.…”
Section: Resultsmentioning
confidence: 99%
“…Each part of the medication process (prescription, transcription, dispensing, administration and monitoring) has been targeted in order to prevent ADEs and potential ADEs and thus improve patient safety. To address each part of the process, several methods have been suggested and carried out such as computerized prescriber order entry (CPOE), decision support with CPOE and clinical pharmacists (for the prescription and transcription parts), bar code technology and automated dispensing cabinets (ADCs) (for the dispensing part) [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…IM-Pharma, another electronic screening system to detect drug-drug interactions, also was shown to reduce the occurrence of inappropriate prescriptions with drug-drug interactions. 20 InterMED-Rx is a software program designed to identify CYP450 drug-drug interactions; its implementation was reported to identify elderly patients at risk for drug-drug interactions. 21 …”
Section: What Should Clinicians and Researchers Do?mentioning
confidence: 99%